Age differences in preferences for body physique. (October 2021) - Han, Chengyang; Lei, Xue; Yan, Panjie; Li, Xiangqian; Morrison, Edward R.
Abstract: Studies have demonstrated the importance of body weight in physical attractiveness, where thinness in women and leanness and muscularity in men are judged to be attractive. However, most research has focused on young adults, while less has investigated whether attractiveness judgments of body weight change with age. Here, we compared young and older adults' preferences for body physique in a Chinese population using 3D human body models. We found that the attractiveness judgments of body physique vary with age, where older adults have weaker preference for thinness in both male and female bodies than did young adults. These results present novel evidence that preferences for body size alters with age. We propose that the variation in preference for thinness is likely due to the difference in resource availability between generations. Highlights: Preferences for body physique vary with age. Older adults have weaker preferences for thinness in both male and female bodies. The association between body physique and attractiveness judgment is quadratic.